Innovative Digital Media in Islamic Religious Education Learning - Septiani Selly Susanti; Laila Nursafitri; Iri Hamzah; Rita Zunarti; Darmanto; Fitriyah; Bima Fandi Asy'arie; Muhammad Syihab As’ad (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – The purpose of this study is to discover and describe the form of innovation in Islamic religious learning that uses digital media/social media as an effective and relevant learning medium in keeping with the demands of technological developments. This study also investigates Islamic Religious Education (PAI) activities in using technology that inspires learning through social media applications. Design/methods/approach – This study used a literature research method with a qualitative approach. Research data was collected from a variety of sources, including books, scientific journals, proceedings, and other relevant publications. This study used a data analysis paradigm that included data collection, reduction, presentation, and conclusion. Findings – The researcher obtained five (5) types of social media applications used by PAI teachers. The study is also restricted by vulnerable years limited to 2019-2023. Accordingly, the social media used by PAI teachers in learning have included (1) Tik-Tok (6 journals), (2) YouTube (10 journals), (3) WhatsApp (9 journals), (4) Facebook (6 journals), and (5) Instagram (5 journals) with a total of 36 journals. PAI teachers have played a role in education transformation by utilizing technology as a more interactive, accessible, effective, and compelling learning medium. Research implications/limitations – The data sources obtained were only limited to online scientific literature. Therefore, the researcher's suggestion for future researchers is to conduct practice field research to allow more accurate results according to the conditions of problems in the field. Originality/Value – The findings of this study provide an overview of the form of learning innovation that has been carried out in PAI learning with the use of digital media. This finding is also a reference for future researchers to make it easier to find a novelty result.